Cu/Fe Bimetallic Treatment Performance on Organophosphorus Pesticides - Wu, Xianpei; Wang, Yanqiong; Xu, Jing; Wang, Hongwu (Frontiers in Environmental Science, 2022)
Typical organophosphorus pesticides, such as glyphosate, trichlorfon, and ethephon, are widely used nowadays, and the treatment of their production wastewater is difficult to achieve by conventional water treatment methods. A Cu/Fe bimetallic system has been proposed as a viable technology to treat toxic and refractory pollutants. The performance of the system with different pH, Cu/Fe molar ratios, Cu/Fe dosages, and initial glyphosate concentrations was analyzed to investigate the operational factors affecting glyphosate removal by the Cu/Fe bimetallic system. Acidic pH (2.0), 100 g iron dosage, 0.25% Cu/Fe, and 60 mg/L initial glyphosate concentration were the appropriate conditions for glyphosate removal, in which the efficiency of the system was in accordance with the pseudo–second-order kinetic model. Under this condition, the removal rates of total phosphorus and total organic carbon reached 99% and 65%, respectively. The Fe/Cu bimetal surface was characterized by scanning electron microscopy, energy-dispersive X-ray spectroscopy, X-ray diffraction, and Fourier transform infrared spectroscopy. Moreover, Fe2+ and Fe3+ were separately applied to treat glyphosate to study their effects on glyphosate removal. The degradation pathway of glyphosate by the Cu/Fe bimetallic system includes C–P and C–N bond cleavage and was achieved through the adsorption and reduction of the Cu/Fe bimetal. whereas the reduction of Fe2+ or the coagulation of Fe3+ contributed less. The optimal conditions for glyphosate decomposition were applied to the treatment of trichlorfon and ethephon. The removal efficiency of the system was poor, but its toxicity to luminescent bacteria Q67 was remarkably reduced.